Impact of Dance on Physical Fitness - Baral, Sujata (Journal of Fine Arts Campus, 2021)
A series of steps and movements that body matches the speed and rhythm of a piece of music is known as Dance. It allows people to be more active, socialize and develop creative and physical skills. Regular exercise has been long associated with a fewer visit to the doctor, hospitalization and medication. Physical activity can help to prevent or manage a wide range of health problems and concerns, including stroke, metabolic syndrome, diabetes, depression, and certain types of cancer, arthritis and falls. The main objective of this study is to analyze and describe the impact of dance on our body and mind. Through this article reader can perceive the significance of dance as physical fitness not only entertainment.